Computational Analysis on Skull Fractures and Brain Injury using Finite Element Analysis - Hazwan Mohamed Norli, Mohd; Al Faiz Hilmi Mohd Al Zahari, Mohammad; Hisyam Marwan, Shahrul; Halim Abdullah, Abdul (International Journal of Engineering and Technology, 2018)
Traumatic Brain Injury (TBI) is a complex injury with a broad spectrum of disabilities and symptoms. Basically it happen when head is impact with certain value of force and the victim has to bear with a certain mechanism of injury. This research has investigated the potential for TBI using Finite Element (FE) analysis with rear impact on the head at different velocities. A 3D human skull and brain were presented and run through simulation in explicit dynamic analysis using commercial finite element software. The risk of skull fractures and brain injury were predicted based on the resulting maximum principal stress, shear strain and total displacement. Final objective of this research is to provide a predictive tool as FE model that can aid in injury diagnosis and design protective devices to minimize the impact effects.Â Â